Pharmacokinetics study of chitosan-coated liposomes containing sumatriptan in the treatment of migraine - Sara Assadpour; Javad Akhtari; Mohammad Reza Shiran (Babol University of Medical Sciences, 2022)
Background: Sumatriptan is a routine medication in the treatment of migraine and cluster headache that is generally given by oral or parental routes. However, a substantial proportion of patients suffer severe side effects. The aim of this study was to investigate the physicochemical characterization and pharmacokinetic parameters of a novel delivery system for sumatriptan succinate (SS) using nanoliposomes (NLs) coated by chitosan (CCLs) to optimize the formulations to enhance its bioavailability. Methods: The new formulation was used to minimize drug particle size and extend its release and bioavailability. The mean particle size and entrapment efficiency for NLs and CCls were optimized and the formulations with better characteristics were chosen for in vivo studies. The concentration-time profile of intravenous SS, intranasal SS, SS-NLs, and CCLs were examined in a rabbit model. Results: The results demonstrated that CCLs were absorbed more rapidly from nasal drops containing chitosan compared to those of SS and SS-NLs as indicated by a shorter tmax, and a higher Cmax in both states. A comparison of the AUC (0-240 min) values revealed that chitosan improved the extent of SS absorption for CCLs formulation. The results of the present study indicated that loading SS into the liposome and coating with chitosan improves drug absorption and a large amount of the drug can be efficiently delivered into the systemic circulation. Conclusion: The liposomal and chitosan formulations of SS had better kinetic behavior than the soluble form in the animal model.